Intestinal Collinsella may mitigate infection and exacerbation of COVID-19 by producing ursodeoxycholate. - Masaaki Hirayama; Hiroshi Nishiwaki; Tomonari Hamaguchi; Mikako Ito; Jun Ueyama; Tetsuya Maeda; Kenichi Kashihara; Yoshio Tsuboi; Kinji Ohno (PLoS ONE, 2021)
The mortality rates of COVID-19 vary widely across countries, but the underlying mechanisms remain unelucidated. We aimed at the elucidation of relationship between gut microbiota and the mortality rates of COVID-19 across countries. Raw sequencing data of 16S rRNA V3-V5 regions of gut microbiota in 953 healthy subjects in ten countries were obtained from the public database. We made a generalized linear model (GLM) to predict the COVID-19 mortality rates using gut microbiota. GLM revealed that low genus Collinsella predicted high COVID-19 mortality rates with a markedly low p-value. Unsupervised clustering of gut microbiota in 953 subjects yielded five enterotypes. The mortality rates were increased from enterotypes 1 to 5, whereas the abundances of Collinsella were decreased from enterotypes 1 to 5 except for enterotype 2. Collinsella produces ursodeoxycholate. Ursodeoxycholate was previously reported to inhibit binding of SARS-CoV-2 to angiotensin-converting enzyme 2; suppress pro-inflammatory cytokines like TNF-α, IL-1β, IL-2, IL-4, and IL-6; have antioxidant and anti-apoptotic effects; and increase alveolar fluid clearance in acute respiratory distress syndrome. Ursodeoxycholate produced by Collinsella may prevent COVID-19 infection and ameliorate acute respiratory distress syndrome in COVID-19 by suppressing cytokine storm syndrome.